Elemental Analysis and Mapping of Some Natural Waters in Eastern Black Sea Region and Investigation of Their Effects on Environment and Human Health - Yaşar Kobya; Cafer Mert Yeşilkanat (Doğal Afetler ve Çevre Dergisi)
In this study, it was aimed to make an elemental analysis of the natural spring waters in 7 cities (Artvin, Rize, Trabzon, Giresun, Ordu, Gümüşhane and Bayburt) in the Eastern Black Sea region and to determine the elemental distribution of the entire region using geostatistical analysis with the help of this analysis. In accordance with this purpose, elemental analyses (Na, Al, P, Cl, K, Ca, V, Mn, Fe, Ni, Cu, Zn) were carried out with the help of ICP-OES device for 40 samples of natural spring water in Eastern Black Sea Region. The average chemical analysis values ​​for each element in Eastern Black Sea Region were as 10270, 215, 122, 4749, 1093, 15960, 59, 5, 89, 18, 10 and 90 μg / L, respectively. The results were generally consistent with the permissible limits of World Health Organization and the Ministry of Health of the Republic of Turkish. In addition, a general harmony was observed as a result of the comparison made with similar studies carried out at different points in the world. Using geostatistical analysis, the distribution of each element was determined and mapped in the study area. By means of these distribution maps, an estimated result could also be obtained about the chemical distributions of waters in unsampled locations. Finally, the possible effects of the analyzed elements on human health and which areas being under risk due to excess elements were discussed in this study.